Structural and reliability analysis of ohmic contacts to SiC with a stable protective coating for harsh environment applications - Daves, Walter; Krauß, Andreas; Häublein, Volker; Bauer, Anton; Frey, Lothar (ECS Journal of Solid State Science and Technology, 2012)
Ohmic contacts to SiC are the most crucial device components for the reliability of SiC devices in harsh environments. This work aimed at improving the reliability of Ni and Ti ohmic contacts to SiC using stable protective coatings. The stability of the contacts was investigated by means of long-term aging at 600°C in air and air/moisture ambient as well as temperature cycling up to 700°C in air/moisture ambient. The structural and chemical properties were investigated by means of XPS depth profiling and TEM analysis. The beneficial effect of a stable protective coating inhibiting the migration of oxygen/moisture into the contact metallization is demonstrated. Excellent reliability benchmarks are shown for Ti ohmic contacts with a PECVD a-SiOx/a-SiC protective coating. The results are very promising for harsh environment applications. © 2012 The Electrochemical Society.